Ginsenosides Improve Nonalcoholic Fatty Liver Disease via Integrated Regulation of Gut Microbiota, Inflammation and Energy Homeostasis - Liang, Wenyi; Zhou, Kun; Jian, Ping; Chang, Zihao; Zhang, Qiunan; Liu, Yuqi; Xiao, Shuiming; Zhang, Lanzhen (Frontiers in Pharmacology, 2021)
Ginseng, the root and rhizome of Panax ginseng C. A. Mey., is a famous herbal medicine, and its major ginsenosides exert beneficial effects on nonalcoholic fatty liver disease (NAFLD). Due to the multicomponent and multitarget features of ginsenosides, their detailed mechanisms remain unclear. This study aimed to explore the role of ginsenoside extract (GE) on NAFLD and the potential mechanisms mediated by the gut microbiota and related molecular processes. C57BL/6J mice were fed a high-fat diet (HFD) supplemented or not supplemented with GE for 12 weeks. A strategy that integrates bacterial gene sequencing, serum pharmacochemistry and network pharmacology was applied. The results showed that GE significantly alleviated HFD-induced NAFLD symptoms in a dose-dependent manner. Furthermore, GE treatment modulated the HFD-induced imbalance in the gut microbiota and alleviated dysbiosis-mediated gut leakage and metabolic endotoxemia. Additionally, 20 components were identified in the mouse plasma after the oral administration of GE, and these interacted with 82 NAFLD-related targets. A network analysis revealed that anti-inflammatory effects and regulation of the metabolic balance might be responsible for the effects of GE on NAFLD. A validation experiment was then conducted, and the results suggested that GE suppressed NF-κB/IκB signaling activation and decreased the release and mRNA levels of proinflammatory factors (TNF-α, IL-1β and IL-6). Additionally, GE promoted hepatic lipolytic genes (CPT-1a), inhibited lipogenic genes (SREBP-1c, FAS, ACC-1) and improved leptin resistance. These findings imply that the benefits of GE are involved in modulating the gut microbiota, enhancing the gut barrier function, restoring the energy balance, and alleviating metabolic inflammation. Moreover, GE might serve as a potential agent for the prevention of NAFLD through the integration of prebiotic, anti-inflammatory and energy-regulatory effects.